The Tasks of the Intermediate Schoolmasters in Reference to Time Administration according to Headmaster’s Viewpoint (Journal of the College of Education for Women, 2018)
The aim of this research is to recognize the tasks undertaken by the headmasters of intermediate schools concerning time- administration, in accordance to the viewpoints of the headmasters of intermediate schools in the Administration of Education of Al-Karkh the Third. The sample of this research consists of (60) headmasters and headmistresses and the tool used on this research was the ‘questionnaire.’ The results of the research showed that in any task undertaken by headmasters without considering time is only a waste and in vain. The correct planning of the task that reconsiders time makes the work more balanced. It is noteworthy that time assigned for a task must be divided correctly according to the plans put whether they are annual or 5-year plans. Also, considering time in any educational planning makes work more disciplined and away from any chaos. According to these results, the research comes up with a number of suggestions and proposals.